Update on Tumor Surveillance for Children with Hereditary Pheochromocytoma/Paraganglioma Syndromes - Rednam, Surya; Kamihara, Junne; Becktell, Kerri D.; Brodeur, Garrett M.; States, Lisa J.; Voss, Stephan D.; Villani, Anita; Zelley, Kristin; Malkin, David; Nakano, Yoshiko; Doria, Andrea S.; Widjaja, Elysa; et al. (Clinical cancer research, 2025)
Hereditary pheochromocytoma/paraganglioma syndromes (HPPS) are a collection of conditions caused by variants in genes producing subunits of the succinate dehydrogenase (SDH) complex or related proteins. These conditions are characterized by substantial lifetime risks for developing pheochromocytomas, paragangliomas, and other tumors. Affected individuals who develop these tumors may experience severe, acute, and chronic problems. Indeed, aggressive, malignant, and/or disseminated tumors may result in death. Tumor surveillance enables early intervention, which, in turn, should lead to improved clinical outcomes. However, the desire for intensive surveillance strategies must be balanced against medical and psychosocial risks. In 2017, consensus HPPS surveillance recommendations addressing germline predisposition to SDHA-, SDHAF2-, SDHB-, SDHC-, SDHD-, MAX-, and TMEM127 (collectively, SDHx+)-related tumors were published after the inaugural American Association for Cancer Research Childhood Cancer Predisposition Workshop. Based on the limited available clinical data at that time, these recommendations advocated a uniform approach to tumor surveillance in HPPS. Since then, several other groups have proposed alternative consensus surveillance guidelines. Although these surveillance approaches share some common elements, including recommendations tailored to emerging differences in tumor phenotype based on underlying specific SDHx+ genes, these approaches also vary significantly among each other. As clinical data continue to accrue, it is critical that surveillance strategies continue to be refined to address emerging genotype-phenotype differences. In this review, we provide a brief up-to-date clinical overview of HPPS and describe recently proposed tumor surveillance regimens. We then detail our updated consensus pediatric-focused tumor surveillance recommendations from the 2023 American Association for Cancer Research Childhood Cancer Predisposition Workshop.
Gesehen am 25.02.2026